DIET IBU MENYUSUI DAN KECUKUPAN AIR SUSU IBU - Widyasih Sunaringtyas; Dhina Widayati (STIKes Adi Husada, 2018)
ABSTRACT Mother breastfeeding Diet is a way how to manage the diet on size, portion and nutritional contents of the food consumed by the breastfeeding mother to meet the needs of breast milk sufficiency for babies. Diets in the form of nutrients will be converted into nutrients so that it becomes a metabolism that serves on producing the breast milk. The purpose of this study was to analyze the relationship of diet with breastfeeding adequacy in breastfeeding mother in Public Healthy Center of Ngadirojo, Pacitan, East Java. The design of this research is correlational research with cross sectional approach. The data as the population in this study were 21 breastfeeding mothers in the Public Health Center, Ngadirojo, Pacitan taken on January, using total sampling technique. Independent variable studied was diet, while the dependent variable in this study was breastfeeding adequacy in reastfeeding mother. Data were obtained questionnaire instrument for diet and observation. The results were analyzed by using spearmen rank test. The results of this study noted that almost all 90.5% maternal breastfeeding diet belonged to enough categories, while 76.2% sufficiency of milk belonged to enough category too. The results of statistical tests known p-value = 0.002 at a significant level (α) = 0.05 and r = 0.647. So it can be concluded that there was a dietary relationship with the adequacy of breast milk. This showed the correlation of strong relationship with positive direction. This means that if the diet is sufficient then the adequacy of breast milk will be enough. So it is expected for breastfeeding mothers to apply a good and proper diet, following health counseling such as maternal breastfeeding diet and exclusive breastfeeding. Keywords: breastfeeding mothers, Diet, Adequacy breastmilk